A Study on the strength of crumb rubber modified bitumen using various crumb rubber sizes - Wan Mohd Fakri, Wan Rahim (2016)
Asphalt use in road pavement because it’s very economical and fulfil the roadway design requirements such as good ride quality, ski –resistance surface, quiet surface and low maintenance. However, consumption of asphalt has some weakness, as it become brittle and hard in cold environments and soft in hot environments hence easy to crack. Besides that, today capacity or volume of the road user that increases year by year is one of the factors that make the road pavement prone to defect or damage such as cracking. Hard traffic and high loading weight also one of the factors affecting the quality of performance pavement and it becomes worst because of overloading on the road. Hence, to reduce damage and defect, an improvised road pavement structures is needed. This experiment will do modified in Asphalt with mix with different crumb rubber (2mm, 0.425mm, and 0.15mm) used as additives. The samples preparation consists of the production of the Marshall Mix specimens. Total of samples is 36 samples will prepare in the laboratory with proper method and apparatus. The samples is designed according to requirement for aggregate course wearing (ACW) using the JKR standard. The range percentage of asphalt was used in this study is 4% until 6%. The size of the sample is same to be prepared 1200 gram plus wastage. From the Marshall Stability and flow test the result is 19.522kN and 18.865kN for experimental samples and constants sample respectively. The conclusion, the crumb rubber can improve the workability, durability and provided higher density of the Hot Mix Asphalt. Furthermore, it gave the pavement a better performance and higher quality pavement for the future development. This finding also helps to save the budget to pavement for the future development. This finding also helps to save the budget to maintain the road in a good condition all the time being. Thus, it is an economical method to be applied in the road construction in order to increase the strength of pavement. In the future, hopefully this finding can encourage new research to be conducted in the different ways and usage.